Dimensi Dakwah Islam dalam Budaya Nyepuh - Muzzammil, Faisal (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2021)
Nyepuh culture is a blend of local wisdom and universal Islamic teachings. The strong interrelation between culture and religion in the reality of Ciomas Village community life seems to be a single dual that is difficult to distinguish. Knowledge is integrated with trust and values, which determines the situation and behavior conditions of Ciomas Village community members. This study aims to reveal the dimensions of Islamic da'wah in the culture of the Nyepuh from the aspects of ideafacts, artifacts, and sociofacts. The theoretical basis of this study refers to the theory of the Three Cultural Beings of J.J. Hoenigman, namely: Ideafacts, Artifacts, and Sociofacts. The findings in the locus study show that: First, the ideafact culture manifestation in the gild culture which has the dimensions of Islamic da'wah includes Mulung Pangpung, Nalekan, Ngasakan, Clean Village, Nya'angan, and Meungkeut Nyere. Second, the artifact culture manifestations in the gild culture with the dimensions of Islamic da'wah are the Sacred Tomb, Golden Geger Water, Pangpung, Tumpeng Rice, Nyere, and Beubeutian. Third, the form of sociofact culture in gild culture has dimensions of Islamic da'wah: Relationship with Humans, Relationship with Nature, and Relationships with God.